Circadian clock components control daily growth activities by modulating cytokinin levels and cell division-associated gene expression in Populus trees - Edwards, Kieron D; Takata, Naoki; Johansson, Mikael; Jurca, Manuela; Novák, Ondřej; Hényková, Eva; Liverani, Silvia; Kozarewa, Iwanka; Strnad, Miroslav; Millar, Andrew J; Ljung, Karin; Eriksson, Maria E (Plant, cell and environment, 2018)
Trees are carbon dioxide sinks and major producers of terrestrial biomass with distinct seasonal growth patterns. Circadian clocks enable the coordination of physiological and biochemical temporal activities, optimally regulating multiple traits including growth. To dissect the clock's role in growth, we analysed Populus tremula × P. tremuloides trees with impaired clock function due to down-regulation of central clock components. late elongated hypocotyl (lhy-10) trees, in which expression of LHY1 and LHY2 is reduced by RNAi, have a short free-running period and show disrupted temporal regulation of gene expression and reduced growth, producing 30-40% less biomass than wild-type trees. Genes important in growth regulation were expressed with an earlier phase in lhy-10, and CYCLIN D3 expression was misaligned and arrhythmic. Levels of cytokinins were lower in lhy-10 trees, which also showed a change in the time of peak expression of genes associated with cell division and growth. However, auxin levels were not altered in lhy-10 trees, and the size of the lignification zone in the stem showed a relative increase. The reduced growth rate and anatomical features of lhy-10 trees were mainly caused by misregulation of cell division, which may have resulted from impaired clock function.
Keywords: mutace; buněčné dělení; Cambium; Populus; geneticky modifikované rostliny; Circadian Clocks; Biomass; cirkadiánní hodiny; Plants, Genetically Modified; kambium; vazba proteinů; Plant Proteins; Indoleacetic Acids; Metabolomics; Mutation; cytokininy; Cytokinins; rostlinné proteiny; stromy; metabolomika; metabolom; kyseliny indoloctové; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; RNA Interference; lignin; Metabolome; RNA interference; Lignin; Trees; Cell Division; biomasa; Protein Binding